What do we know about early sport specialization? Not much! - Baker, J.; Cobley, S.; Fraser-Thomas, J. (High Ability Studies, 2009)
In November 2005, the International Olympic Committee`s Medical Commission issued a statement on Training the elite child athlete recommending that "more scientific research be done to better identify the parameters of training the elite child athlete". This paper focuses on a specific issue related to training the child athlete: early specialization. While associations between early specialization and expertise development are highlighted, much research also suggests early specialization is associated with a range of negative consequences affecting physical, psychological, and social development. Alternately, some researchers have proposed that an early diversification approach does not disadvantage athletes in acquiring expertise, and is important for the development of intrinsic motivation and skill transferability. However, this review suggests that inadequate evidence exists to resolve the issue in favor of either approach.